2013
DOI: 10.1177/0020852313489945
|View full text |Cite
|
Sign up to set email alerts
|

Public sector leadership: new perspectives for research and practice

Abstract: In this article, we aim to portray the state of the art in public sector leadership in order to recommend directions for research and training practice. To this end, we review the scattered strands of literature on public sector leadership (PSL) and classify them in a single framework. The results of the study suggest that public sector leadership is emerging as a distinctive and autonomous domain in public administration/public management studies, although the debate is still underdeveloped compared to busine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
145
0
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(168 citation statements)
references
References 60 publications
4
145
0
19
Order By: Relevance
“…For example, Kim and Lee (2009) investigated management capacity in the innovation process in the Korean public sector and highlighted the importance of innovative leadership on the adoption and implementation of innovations. The willingness of leaders to take risks on novel initiatives and adopt fresh perspectives is the main factor in the success of innovation implementation (Orazi et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Kim and Lee (2009) investigated management capacity in the innovation process in the Korean public sector and highlighted the importance of innovative leadership on the adoption and implementation of innovations. The willingness of leaders to take risks on novel initiatives and adopt fresh perspectives is the main factor in the success of innovation implementation (Orazi et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main key to innovation in public sector is the role of administrative leadership in improving the performance of public sector oganization (Orazi et al, 2013). In our study, we found that the head of regency government and the secretary of regency showed a strong commitment of preserving transparency and accountability values in managing public funds.…”
Section: E Discussionmentioning
confidence: 68%
“…Van Wart (: 218) noted the expansion of the literature on administrative leadership in the 1990s, but nonetheless characterized its overall development as “relatively unfocused” and constituting “a fraction of that in the private sector.” In the decade that followed, however, there was a proliferation of scholarship on public sector leadership (Orazi, Turrini, and Valotti ; Van Wart ). These studies, written primarily by American and European academics, employed a range of research methods (from data based studies to single and comparative case studies to theoretical contributions) and addressed a wide range of topics germane to administrative leadership.…”
Section: Administrative Leadership In Public Organizationsmentioning
confidence: 99%